Estimation of Demand for Forest Recreation (Camping) a Conceptual Frame Work - Chowdhary, R. L. (Indian Forester, 1977)
The paper aims to provide conceptual frame work for quantification of consumer benefits from outdoor forest recreation-namely camping. Utilising the data of camper survey carried out by the author in Earl Rowe Provincial Park, in Alliston Ontario, Canada, the camping season of 151 days is divided in to 5 experience types. The consumer surplus of each camper in each of the experience type and in each income category, has been estimated after deducting his fixed expenditure from the fixed expenditure of highest cost visitor in each income group and each experience type. Arranging the consumer surplus in descending order of magnitude, irrespective of income category, a relationship between consumer surplus and camper days was obtained. To convert camper days to campsite, the following logic was used: The total consumer surplus provided by one campsite in experience type I will be an aggregation of highest 12 consumer surplus per camper day. The sum of the next 12 highest consumer surplus will give a net value of the second campsite for experience type I. By such successive aggregation of consumer surplus of 12 visitor days, the net benefit for each campsite was obtained. When plotted, t his would give a convention demand curve for experience type I. Similar demand curves were obtained for the other 3 experience types. A correction was made in consumer surplus for each experience type by addition of campsite fee of $ 2.50 per day, The operating expenses Were substracted from consumer surplus to give the net consumer surplus due to capital facilities on]y, By vertical addition of the demand curve for each experience type, an aggregate demand curve for campsites for Earl Rowe Provincial Park in 1971, was obtained, The optimum capacity of campsites in the Park was determined from the intersection of aggregate demand curve for campsites and average cost curve for campsites. In case of Earl Rowe Park, the optimum capacity for 1971 was 370. Discriminatory pricing pattern is suggested for pricing of campsites. The daily price to be charged was obtained from the intersection of demand curve for each Experience type with average cost curve. The daily toll for entrance to campsite for Experience type I, II, III and IV for Earl Rowe Park in 1971 works out to respectively 8 6.07 , 8161, $ 0.44, and;$ 0.44 as against at uniform. toll of 5 2.50 charges for all Experience type. No toll is proposed to be levied for experence type V and operating expenses during this period are recommended to be brought to minimum.